2015
DOI: 10.1073/pnas.1422096112
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modification of the oxytocin receptor gene influences the perception of anger and fear in the human brain

Abstract: In humans, the neuropeptide oxytocin plays a critical role in social and emotional behavior. The actions of this molecule are dependent on a protein that acts as its receptor, which is encoded by the oxytocin receptor gene (OXTR). DNA methylation of OXTR, an epigenetic modification, directly influences gene transcription and is variable in humans. However, the impact of this variability on specific social behaviors is unknown. We hypothesized that variability in OXTR methylation impacts social perceptual proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
158
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(174 citation statements)
references
References 75 publications
13
158
1
2
Order By: Relevance
“…Further evidence that individual differences in sensitivity to socially relevant stimuli may be related to oxytocin functions comes from several recent epigenetic studies (Jack et al, 2012;Puglia et al, 2015). The first reported that DNA methylation at the OXTR was predictive of an individual's neural response to biological motion (Jack et al, 2012).…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensory mentioning
confidence: 99%
“…Further evidence that individual differences in sensitivity to socially relevant stimuli may be related to oxytocin functions comes from several recent epigenetic studies (Jack et al, 2012;Puglia et al, 2015). The first reported that DNA methylation at the OXTR was predictive of an individual's neural response to biological motion (Jack et al, 2012).…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensory mentioning
confidence: 99%
“…In addition to sequence variations in OT pathway genes, epigenetic modifications of the OXTR gene have recently attracted considerable attention in clinical, behavioral, and cognitive neurosciences (Kumsta et al, 2013) and have been associated with different phenotypes including maternal PPD (Bell et al, 2015; Kimmel et al, 2016), amygdala reactivity (Puglia et al, 2015), autism (Gregory et al, 2009), and social anxiety disorder (Ziegler et al, 2015) amongst others. Briefly, epigenetics encompasses a set of biochemical modifications of genome function (e.g., histone modifications, DNA methylation, or the effects of small non-coding RNAs, e.g., micro RNAs) that interfere with transcriptional or translational events and can therefore regulate gene expression.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
“…Effects of maternal care were small, however, and phenotypic differences (i.e., higher depression risk) that could link these differentially methylated regions to variation in observable behavior were not assessed. It has been recently shown that increased peripheral blood cell OXTR promoter methylation at CpG −934 is correlated with higher amygdala reactivity and also with lower functional connectivity between right amygdala and brain areas involved in emotion regulation (cingulate and orbitofrontal cortex), suggesting an inhibition of top-down regulation of the amygdala (Puglia et al, 2015). This finding provides first evidence of the predictive value of peripheral OXTR methylation in explaining variability of functional alterations in brain areas that are key in modulation of affective states.…”
Section: Gene-environment Interactions and Epigenetic Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…2002) and is modulated by other relevant genetic and epigenetic biomarkers for social behavior like those related to oxytocin (Puglia et al. 2015). Furthermore, some data suggest that the same neural systems activated during the identification of a particular emotion in others also respond to the personal experience of this emotion (Assogna et al.…”
Section: Discussionmentioning
confidence: 99%